Social Transformation and Civil Society: Dr.B.R. Ambedkar Perspective - Nagaraju N., (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
Dr B R Ambedkar was the champion of social justice, he just not work for a particular section he was serve for whole nation by changing the social system. He was struggle for social transformation of traditional hierarchical society into civil society with the aim of brings socio-economic and political equality among the Indians with intention of develops the brotherhood. Ambedkar regarded India is home of social inequality therefore he put his effort to bring constitutional remedies for all sort of inequality and discrimination. Ambedkar provided all kind of equal opportunity in education, rights, power and participation in decision making process in that way Ambedkar real champion of civil society and India must remember Ambedkar is father of civil society of India.
Keywords: Social Transformation; Civil Society; Civil Rights; Equal Opportunities; Democratic Civil Society